Community Service Through Education to Recognize and Appreciate Rupiah from an Early Age for Students of SDN 2 Kopyah Indramayu - Meida Tisnawati Putri; Didik Himmawan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The supporting program for the KKN PPM activities of Wiralodra University in Kopyah Village, Anjatan District, Indramayu Regency, was implemented at UPTD SDN 2 Kopyah. UPTD SDN 2 Kopyah is a state-owned education institution and operates at the elementary school level. The total number of students is 271 students, divided into 6 classes, with an average of 40 students per class. The number of students in each class has met the class management standards. Based on initial observations made by the author to the principal of UPTD SDN 2 Kopyah, students are still not familiar with CBP Rupiah but are already familiar with and implementing a savings system. This is due to several factors, including the elementary school curriculum often does not explicitly cover topics related to CBP Rupiah, so students do not receive formal learning about this; elementary schools focus more on core subjects; and the lack of socialization programs aimed at elementary school children regarding the importance of CBP Rupiah. In contrast to the savings education implemented at UPTD SDN 2 Kopyah, students already know about the theory given, but in practice students still do not fully understand the benefits and objectives of saving properly. Therefore, the author has an initiative to provide a solution to this problem, namely by providing simple education and implementation about CBP Rupiah and saving for elementary school students. This aims to increase basic knowledge and understanding of finance for students, including the importance of knowing and using the national currency. Educating elementary school students about CBP Rupiah and saving has important benefits and objectives for their development. The benefits include introducing the value of money, basic financial skills, financial independence, character education, and preventing consumerism. Through this education, students learn to recognize and understand the value of money, so that they can be wiser in using it. They get the basics of financial skills such as saving, budgeting, and understanding the concept of spending. This helps them become more financially independent from an early age, which is important for their future. The delivery method that the author will use is by face to face interaction directly with students in class, there is a PPT and educational video delivery about CBP Rupiah and saving, providing media for them to save money and some bills as a practice media to get to know CBP Rupiah. The output target of the